Microsoft Windows Vista management and administration - Abbate, Andrew (Sams, 2008)
"This book will show administrators how to manage and administer the advanced functions and security features in Windows Vista. The authors highlight the functions of Windows Vista that both large and small environments have found to be the most useful, including all-new features such as Complete PC Backup, BitLocker, and the powerful Group Policy options that are only available in Windows Vista."--Jacket
Print version record
Keywords: Microsoft Windows (Computer file); Operating systems (Computers); Systèmes d'exploitation (Ordinateurs); operating systems